Microtus quasiater (Rodentia: Cricetidae). (22nd August 2018) - Torres-Flores, José Williams; López-Wilchis, Ricardo
Abstract: Microtus quasiater (Coues, 1874) is a small arvicoline rodent commonly known as the Jalapan pine vole. It is 1 of 7 species of Microtus that live in Mexico. M. quasiater has a restricted distribution, and typically inhabits mountain cloud forest in the Sierra Madre Oriental along a narrow zone at elevations from about 700 to 2, 150 m. It is a generalist herbivore known to feed on at least 36 plant species, including both monocotyledons and dicotyledons. The species is considered as "Near Threatened" by the International Union for Conservation of Nature and Natural Resources and some data indicate low population sizes.